Tunability of morphological properties of Nd-doped TiO2 thin films. (16th November 2016) - Rehan, Imran; Sultana, Sabiha; Khan, Nauman; Qamar, Zahid; Rehan, Kamran
Abstract: In this work, an endeavor is made toward structural assessment and morphological variation of titanium dioxide (TiO2 ) thin films when doped with neodymium (Nd). The electron beam deposition technique was employed to fabricate Nd-based TiO2 thin films on n-Type Si substrates. Nd concentration was varied from 0.0 to 2.0 atomic percent (at.%) under identical growth environments. The films were deposited in an oxygen-deficient environment to cause the growth of rutile phases. Energy dispersive x-ray spectroscopy confirmed the presence and variation of Nd dopant in TiO2 . X-ray diffraction analysis showed the transformation of amorphous structures of the as-grown samples to anatase polycrystalline after annealing at 500 °C, while atomic force microscopy exposed linearity in grain density in as-grown samples with doping until 1 at.%. Raman spectrums of as-grown and annealed samples revealed the growth of the anatase phase in the annealed samples. Based on these results it can be proposed that Nd doping has pronounced effects on the structural characteristics of TiO2 thin films.